Get the edge - Beattie, Geoffrey (London : Headline Business Plus, 2011)
Leading psychologist Geoff Beattie draws on cutting-edge research to answer all these questions and many more in this fascinating guide to getting what you want. With his insight into what makes us tick, he provides us with quick tips that will help to shake off your old, bad habits and quickly get into new, positive ones.
Includes bibliographical references (pages 303-317) and index.
Keywords: Body language; Interpersonal communication; Self-help techniques; Body language; Interpersonal communication; Self-help techniques